Collaborative Documentary Photo Projects: from Techno-utopia to Imagined Community - Karine Chambefort-Kay (Transatlantica)
This article studies three collaborative documentary photographic projects, The Polling Place Photo Project, Mapping Main Street (United States, 2008 and 2009) and Simon Roberts’s Election Project (Great Britain, 2010), which operated with similar goals and modes—to re-engage the public and citizens by committing them to building an online archive of images. The features of the collaborative documentary mode are analysed as a number of strategies involving the authority of amateurs, forms of crowdsourcing and a new kind of agency as photographs are produced by multiple contributors and displayed online. As these strategies seem to be photographic emulations of the democratic process, the question arises of the apparent correspondence between such strategies and the explicit purpose of enhancing citizenship and democracy or fostering involvement and community. Is the medium the message in collaborative documentary? This study shows the limits of a technology-oriented approach to the collaborative documentary and proposes to direct attention to the social, political and historical context of the three projects and to their contents: instead of mere experiments in collaborative photographic practices, the archives may be construed as public spheres for collective self-imagining, and in particular for imagining the national community.